Francisco Moreno Fernández: Variedades de la lengua española. London/New York: Routledge, 2020, 186 pp. ISBN 978-1138385955. - Ruiz-González, Natalia (Philologia Hispalensis, 2021)
Reseña de Francisco Moreno Fernández: Variedades de la lengua española. London/New York: Routledge, 2020.